The Alaskan Arctic regime shift since 2017: A harbinger of years to come? - Ballinger, Thomas J.; Overland, James E. (Polar Science, 2022)
Recent fingerprints of Alaskan Arctic climate change include new weather patterns whose impacts propagate through the Alaskan marine ecosystem. Multiple lines of observational evidence draw attention to the last five years (2017–2021) as a remarkable period of change. Bering Sea winter and spring ice coverage was remarkably low in 2018 and 2019 associated with a shifted Aleutian Low (AL) into the western Bering Sea, and ridging of the overlying polar jet stream (PJS) that supported southerly winds and reduced ice growth. The climatological Beaufort High and associated Beaufort Gyre saw multiple winter-long collapses (2017 and 2020), the only two such events of the modern reanalysis era. In contrast, from 2012 to 2016 the AL and PJS were located southeastward across the Gulf of Alaska, which supported sea ice growth. The recent collocation of the exposed ocean surface and atmospheric anomalies supports the emergence of a regional atmospheric circulation response to sea-ice loss. We propose that the regional system shift after 2017 foreshadows the beginning of a period with an increasing frequency of major sea-ice loss events and associated impacts – floods, delayed spring blooms, and marine food chain disruptions – which is sooner than projected by climate models. journal article